Morphology, Molecular Phylogeny, and Fungicide Sensitivity of Phytophthora nagaii and P. tentaculata in Korea - Seung Hyun Lee; Bora Nam; Dong Jae Lee; Young-Joon Choi (Mycobiology, 2023)
AbstractPhytophthora species, classified under Oomycota, cause significant damage to various crops and trees. The present study introduced Phytophthora species, P. nagaii and P. tentaculata, new to Korea, which pose notable risks to their respective host plants. Our research provided a comprehensive description of these species taking into account their cultural features, morphological characteristics, and molecular phylogenetic analysis using the internal transcribed spacer rDNA region and cytochrome c oxidase subunit mtDNA genes (cox1 and cox2) sequences. In addition, this study first evaluated the sensitivity of P. nagaii and P. tentaculata to five anti-oomycete fungicides, finding both species most responsive to picarbutrazox and P. tentaculata resistant to fluazinam. The data can guide targeted treatment strategies and offer insights into effective control methods. The findings expand our understanding of the diversity, distribution, and management of Phytophthora species in Korea.